Synthesis, structural and spectroscopic properties of Co(II), Ni(II) and Cu(II) complexes with 2-((2-chlorobenzylidene)amino) acetohydrazide hydrate and their Antimicrobial and antioxidant activities - Al-Azab, Fathi Mohammed; Jamil, Yasmin Mosa’d; Al-Gaadbi, Amani Ahmed (Eclética Química, 2023)
The current study was purposed to prepare Co(II), Ni(II) and Cu(II) complexes with the ligands derived from 2-chlorobenzaldehyde, glycine and hydrazine hydrate. The obtained compounds were characterized by different physicochemical studies such as elemental analysis, atomic absorption, molar ratio analysis, electronic absorption (UV-Vis spectroscopy), magnetic properties, FTIR spectroscopy, 1H–NMR, 13C-NMR, conductance measurements and XRD. Antimicrobial and antioxidant activities were also calculated. The antibacterial activity was evaluated by the diffusion method against two Gram-positive and two Gram-negative bacteria, while antifungal activity was assessed against two fungal strains by using the agar method. The ligand with Schiff base and hydrazide groups and its complexes showed better biological activity. The results showed that the most metal complexes have much higher antibacterial and antifungal activity compared to the parent ligand. The antioxidant activity of 3.7453 mg of the ligand exhibited excellent activity as the activity of 1 mg of ascorbic acid which is used as a standard antioxidant.